Immediate-Early, Early, and Late Responses to DNA Double Stranded Breaks - Kieffer, Shaylee R.; Lowndes, Noel F. (Frontiers in Genetics, 2022)
Loss or rearrangement of genetic information can result from incorrect responses to DNA double strand breaks (DSBs). The cellular responses to DSBs encompass a range of highly coordinated events designed to detect and respond appropriately to the damage, thereby preserving genomic integrity. In analogy with events occurring during viral infection, we appropriate the terms Immediate-Early, Early, and Late to describe the pre-repair responses to DSBs. A distinguishing feature of the Immediate-Early response is that the large protein condensates that form during the Early and Late response and are resolved upon repair, termed foci, are not visible. The Immediate-Early response encompasses initial lesion sensing, involving poly (ADP-ribose) polymerases (PARPs), KU70/80, and MRN, as well as rapid repair by so-called ‘fast-kinetic’ canonical non-homologous end joining (cNHEJ). Initial binding of PARPs and the KU70/80 complex to breaks appears to be mutually exclusive at easily ligatable DSBs that are repaired efficiently by fast-kinetic cNHEJ; a process that is PARP-, ATM-, 53BP1-, Artemis-, and resection-independent. However, at more complex breaks requiring processing, the Immediate-Early response involving PARPs and the ensuing highly dynamic PARylation (polyADP ribosylation) of many substrates may aid recruitment of both KU70/80 and MRN to DSBs. Complex DSBs rely upon the Early response, largely defined by ATM-dependent focal recruitment of many signalling molecules into large condensates, and regulated by complex chromatin dynamics. Finally, the Late response integrates information from cell cycle phase, chromatin context, and type of DSB to determine appropriate pathway choice. Critical to pathway choice is the recruitment of p53 binding protein 1 (53BP1) and breast cancer associated 1 (BRCA1). However, additional factors recruited throughout the DSB response also impact upon pathway choice, although these remain to be fully characterised. The Late response somehow channels DSBs into the appropriate high-fidelity repair pathway, typically either ‘slow-kinetic’ cNHEJ or homologous recombination (HR). Loss of specific components of the DSB repair machinery results in cells utilising remaining factors to effect repair, but often at the cost of increased mutagenesis. Here we discuss the complex regulation of the Immediate-Early, Early, and Late responses to DSBs proceeding repair itself.